Communalities of meanings for Mexican traditional cheeses: Zacazonapan cheese, Quesillo and Poro cheese - Hernández-Montes, Arturo; Torres-Salas, Verenice; Pablo-Cano, Magdiel; Jáuregui-García, Carla Zulema; Peralta-Aparicio, Celia; Espejel-García, Anastacio (Acta Universitaria, 2020)
Traditional cheeses are associated with their place of origin and should have an identity of meaning for consumers. The aim of this research was to identify communalities of meanings in consumers of Zacazonapan cheese, Quesillo and Poro cheese. A survey was applied to 200 consumers of each cheese. In the survey, an image of the cheese was shown to the participants, and then they were asked to write three words associated with the image. The words produced were grouped by affinity, and a k-proportions test and the Marascuilo procedure were applied to their frequencies. The Quesillo (69.3%) and the Poro cheese (72.2%) presented greater symbolic psychological meanings than the Zacazonapan cheese (48.1%). Within these meanings, the communality for the meaning of identity was notable. The Quesillo and the Poro cheese were valued for their intangible aspects and were associated with their place of origin.